Digital Startup "Veggie Fresh" using Code Igniter and Design Thinking Method - Akhlak, Muhammad Lutfi Mahasinul; Winanto, Andri; Yuliana, Devi; Ayuningtyas, Anastasia Riesa (Innovation, Technology, and Entrepreneurship Journal, 2025)
This study aims to create a digital startup with an e-commerce platform named VeggieFresh that provides fresh vegetables directly from farmers to consumers. This startup has effectively answered user needs by making it easier for customers to buy fresh and quality vegetables without having to leave home. The VeggieFresh startup also helps farmers market their agricultural products more effectively and efficiently. The method used is Design Thinking, which focuses on a deep understanding of user needs and creating innovative solutions. Design Thinking stages such as Empathize, Define, Ideate, Prototype, and Test are applied to identify challenges customers and farmers face, formulate appropriate solutions, and test the prototypes created. The analysis used is SWOT analysis and TELOS feasibility analysis. The user interface design uses the GSTALT principle to make the appearance more elegant and responsive. The prototype developed got a positive response from users with the results of the Usability Heuristic test of 82%. This shows that this startup has met user needs with an intuitive and user-friendly interface. Thus, VeggieFresh has great potential to become an effective e-commerce solution that connects farmers and consumers and increases efficiency and convenience in shopping for fresh vegetables.